PENGARUH PEMBERIAN PUPUK BOKASHI FESES SAPI SUMBA ONGOLE TERHADAP PERTUMBUHAN LEUCAENA LEUCOCEPHALA CV. TARRAMBA - Ferdianto Bulu; Marselinus Hambakodu (JURNAL PETERNAKAN SABANA, 2022)
The aims of the experiment was to determine the effect of bokashi fertilizer Sumba Ongole cattle fecess on growth of lamtoro taramba (Leucaena leucocephala cv. tarramba). Theexperiment has been carried out in Animal Feed Forage, Agricultural and Livestock Field Laboratory, Kuta Village, Kanatang District, East Sumba Regency for 3 months. Theexperiment used a completely randomized design (CRD) with 5 treatments and 4 replications such as ; PO: without bokashi fertilizer, Sumba Ongole cattle faeces, P1: bokashi fertilizer for Sumba Ongole cattle feces 200 grams/planting hole, P2: bokashi fertilizer for Sumba Ongole cattle feces 500 grams/planting hole, P3: bokashi fertilizer for Sumba Ongole cattle feces 800 grams/hole planting, P4: bokashi fertilizer for Sumba Ongole cattle feces 1000 grams/planting hole. The variables observed in this experimentwere plant height, total of leaves, stem diameter, fresh weight and dry weight. The results showed that the giving of bokashi fertilizer on Sumba Ongole cattle had a significant effect (P<0.05) on plant height, total of leaves, stem diameter, fresh weight and dry weight. In conclusion, the giving of bokashi fertilizer for Sumba ongole cattle for level of 800 grams/planting hole increased the growth and productivity of lamtoro taramba (Leucaena leucocephala cv. tarramba).